The financial market and its role in mobilizing additional sources of financing ("Journal "U". Economy. Management. Finance.", 2024)
This article examines the role of the financial market as a key mechanism for mobilizing additional sources of financing for companies, organizations and government agencies. Various instruments and mechanisms used in financial markets, such as equity, bond issuance, lending, derivatives and venture capital, are analyzed. The role of the financial market in stimulating economic growth and development through providing access to capital for business expansion, investment in innovations and new projects is considered.
Keywords: financial market; sources of financing; mechanisms of resource mobilization